A shielding glass and its preparation method

By selecting PMMA sheets and UV glue, and modifying and curing process optimization, the problem of bubbles and glue opening in the electromagnetic shielded glass at a high temperature of 85℃ is solved, achieving higher high-temperature resistance.

CN119369744BActive Publication Date: 2025-03-18北京泰派斯特电子技术有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411918287.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

Existing electromagnetic shielded glass is prone to bubbles and glue opening in a high temperature environment of 85℃, which cannot meet the usage requirements in a high temperature environment.

Method used

PMMA sheets are used as transparent substrates, combined with UV glue as adhesive material, and the high temperature resistance of shielded glass is improved by modifying PMMA sheets and optimizing the UV curing process.

Benefits of technology

Within 48 hours under high temperature conditions of 85°C, the prepared shielded glass does not produce bubbles and does not open glue, which significantly improves its high temperature resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119369744B_ABST
    Figure CN119369744B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of electromagnetic shielding glass manufacturing, and the present application discloses a shielding glass and a preparation method. The preparation method of the shielding glass in the present application includes the following steps: dispensing glue on the PMMA sheet, covering with a metal mesh, combining the sheets, vacuum degassing and UV curing. The present application improves the adhesion and light transmittance between the transparent substrate and the adhesive material by selecting the PMMA sheet as the transparent substrate and the UV glue as the adhesive material, and improves the high temperature resistance of the shielding glass by modifying the PMMA sheet, selecting a suitable UV glue and the UV curing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electromagnetic shielding glass manufacturing, and in particular to a shielding glass and a preparation method thereof. Background Art

[0002] On the one hand, electromagnetic shielding glass is used to seal the source of electromagnetic interference and reduce the electromagnetic interference of the electromagnetic interference source to the outside world. On the other hand, it can also be used to seal electromagnetic sensitive circuits to protect the circuits and avoid external electromagnetic interference. It has both light transmittance and electromagnetic shielding capabilities.

[0003] At present, there are three main types of electromagnetic shielding glass. The first is to form a conductive film on the surface of a transparent substrate, the second is to use a transparent substrate to clamp a conductive wire mesh, and the third is to use the above two methods at the same time. The technology of using a transparent substrate to clamp a conductive wire mesh has become the mainstream production technology for electromagnetic shielding glass because of its high efficiency and low cost. At present, electronic equipment uses flexible shielding windows with wire mesh. The substrate of the flexible shielding window is made of acrylic board or PC board. The adhesive layer material usually selected is EVA. Since the softening temperature of EVA is 55℃-60℃, it is difficult to meet the requirements of no debonding and no bubbles in a high temperature environment of 85℃. If the environmental temperature index is improved, rigid float glass is used as the supporting material, and the PVB adhesive layer is used, it can usually meet the high temperature environment of 70℃. If it is to meet the requirements of no debonding and no bubbles in a high temperature environment of 85℃, further process optimization is required.

[0004] The shielding window with acrylic as the base material is not resistant to high temperature because acrylic expands and absorbs water and warps at the four corners in a high temperature and high humidity environment; and the bonding strength of the adhesive becomes lower in a high temperature and high humidity environment. In the high and low temperature and wet heat serial test, as the thermal expansion and warping of the board produce internal stress, the bonding strength of the adhesive layer cannot offset the internal stress of the acrylic deformation, causing cracking. The adhesive is not resistant to high temperatures of 85°C, causing blistering and edge cracking. Summary of the invention

[0005] In order to improve the problem that shielding glass is prone to bubbles or even debonding under high temperature conditions, the present application provides a shielding glass and a preparation method thereof.

[0006] In a first aspect, the present application provides a method for preparing shielding glass, comprising the following steps:

[0007] S1. Place the PMMA sheet on the operating table, apply UV glue on the PMMA sheet, and let it stand for self-leveling;

[0008] S2, covering the cut metal mesh on the PMMA plate after the glue is dispensed in step S1, and set aside;

[0009] S3, repeat the operation of step S1 to obtain another PMMA sheet with glue applied, for later use;

[0010] S4, pressing the PMMA sheet in step S2 and the PMMA sheet in step S3 together

[0011] A composite sheet is prepared, wherein the composite sheet is composed of a PMMA sheet, a UV adhesive, a metal mesh, a UV adhesive and a PMMA sheet from bottom to top;

[0012] S5, pre-pressing the combined sheet obtained in step S4 under vacuum to remove bubbles;

[0013] S6, curing the combined sheets after degassing in step S5 under UV light to obtain shielding glass.

[0014] By adopting the above technical solution, the organic sheet is used as a transparent substrate in this application, which has the characteristics of impact resistance, light weight, high strength, good environmental resistance and cold bending. Combined with the characteristics of PMMA being easy to soften at 85°C, PMMA is modified or compounded to improve its high temperature resistance and bending resistance. UV glue is acrylic glue, also known as acrylic glue. According to the principle of polymer similarity, compatibility and bonding force, UV glue is preferably used. This application combines the traditional screen full lamination process with the electromagnetic shielding process, and the product produced has a high yield rate and good defoaming effect.

[0015] Preferably, the curing shrinkage of the UV glue is 2-2.6%, the refractive index of the UV glue is 1.47-1.48, and the transmittance of the UV glue to visible light with a wavelength of 550 nm is more than 99%.

[0016] By adopting the above technical solution, the UV glue used in this application has good light transmittance, is colorless and transparent, has a light transmittance of more than 99%, good bonding strength, and simple curing conditions. It also has the characteristics of small curing shrinkage and yellowing resistance, and the product will not yellow, peel or deteriorate after long-term use. It also significantly enhances the light transmittance of electromagnetic glass and the mechanical properties of electromagnetic shielding glass.

[0017] Optionally, in step S6, curing is divided into pre-curing and main curing, the pre-curing time is 15-60s, and the main curing time is 0.5-3h.

[0018] Optionally, in step S6, the UV light source is selected from at least one of a mercury lamp light source, an LED light source, and a xenon lamp light source, and the curing energy is 5000-12000 mJ / cm 2 .

[0019] By adopting the above technical solution, there is a certain positive relationship between the pressure of the press bonding and the curing degree of the pre-curing, and the pressure is also adjusted accordingly according to the bonding area. This application selects the pre-curing degree according to the bonding requirements. The precise control of the pre-curing degree can be achieved by tracking the curing process through real-time infrared spectroscopy, so as to grasp the pre-curing degree and the curing degree through the pre-curing time, UV light source and curing energy. The curing energy is controlled at 2000-12000mJ / cm 2 If the value is too low, the bonding strength will be insufficient, while if it is too high, the UV glue will deteriorate or produce bubbles.

[0020] Optionally, the viscosity of the UV glue is 800mps-1500mps.

[0021] Optionally, the thickness of a single layer of PMMA sheet in the composite sheet is 0.9-1.2 mm, and the thickness of a single layer of UV glue in the composite sheet is 0.1-0.2 mm.

[0022] Optionally, the raw material of the PMMA plate includes 0-7.5wt% of modified PMMA.

[0023] Preferably, the PMMA sheet includes 6 wt % of modified PMMA.

[0024] By adding an appropriate amount of modified PMMA, while maintaining a high light transmittance of the modified PMMA sheet, the high temperature resistance of the modified PMMA sheet is improved, and the internal stress caused by thermal expansion and warping of the modified PMMA sheet is reduced, so that the bonding strength of the UV adhesive layer can offset the internal stress of acrylic deformation, so that the modified PMMA sheet will not debond at a higher temperature, thereby maintaining the high temperature resistance and light transmittance of the shielding glass at a high level.

[0025] Optionally, the preparation method of the modified PMMA includes:

[0026] (1) Add nano calcium carbonate to a 30 wt% sodium phosphate solution, let stand for 20-40 min, take out, and dry; immerse in octadecyltrichlorosilane liquid for 15-30 min, dry, and obtain modified nano calcium carbonate for later use;

[0027] (2) Add methyl methacrylate, polyvinyl pyrrolidone and initiator to the solvent, stir at 60-90°C for 1.5-3h, add zinc stearate and modified nano calcium carbonate prepared in step (1), continue stirring at 60-90°C for 3-4h, filter, take the filter residue, dry at 60-80°C for 12-24h, and granulate to obtain modified PMMA.

[0028] By adopting the above technical scheme, the surface of the nano calcium carbonate pretreated with sodium phosphate solution is connected with active groups such as P-OH, and then treated with octadecyltrichlorosilane. When in-situ polymerization is carried out with methyl methacrylate, the compatibility of the modified nano calcium carbonate with methyl methacrylate is greatly improved, and the in-situ polymerization modification can effectively improve the hydrophobic and lipophilic properties of the nano calcium carbonate, and can make the modified calcium carbonate evenly distributed in PMMA. After the nano calcium carbonate is treated with sodium phosphate and octadecyltrichlorosilane, the heat resistance and mechanical properties are greatly improved, so that the modified PMMA has good temperature resistance and mechanical strength.

[0029] Optionally, the modified PMMA comprises the following raw materials in parts by weight: 60-90 parts of methyl methacrylate, 6-13 parts of modified nano-calcium carbonate, 3-5 parts of zinc stearate, 1.5-3.5 parts of polyvinyl pyrrolidone and 0.5-0.9 parts of initiator; in the preparation process of the modified nano-calcium carbonate, the weight ratio of the nano-calcium carbonate, sodium phosphate solution and octadecyltrichlorosilane is: 8-12:40-60:15-25.

[0030] In a second aspect, the present application provides a shielding glass manufactured according to the above-mentioned method for manufacturing shielding glass.

[0031] In summary, the present invention includes at least one of the following beneficial technical effects:

[0032] 1. The application selects PMMA sheet as the transparent substrate and UV glue as the bonding material to improve the adhesion and light transmittance between the transparent substrate and the bonding material. The high temperature resistance of the shielding glass is improved by modifying the PMMA sheet, selecting appropriate UV glue and UV curing process.

[0033] 2. The shielding glass prepared in the present application does not generate bubbles and does not debond within 48 hours under a high temperature condition of 85°C, thereby improving the high temperature resistance of the prepared shielding glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a schematic diagram of the overall structure of the shielding glass provided by the present application;

[0035] Explanation of the accompanying drawings: 1. One layer of PMMA sheet; 2. One layer of UV glue; 3. Metal mesh; 4. Another layer of UV glue; 5. Another layer of PMMA sheet. DETAILED DESCRIPTION

[0036] The present application is further described in detail below in conjunction with embodiments.

[0037] The present application provides a method for preparing shielding glass, comprising the following steps:

[0038] S1. Place the PMMA sheet on the operating table, apply UV glue on the PMMA sheet, and let it stand for self-leveling;

[0039] S2, covering the cut metal mesh on the PMMA plate after the glue is dispensed in step S1, and set aside;

[0040] S3, repeat the operation of step S1 to obtain another PMMA sheet with glue applied, for later use;

[0041] S4, pressing the PMMA sheet in step S2 and the PMMA sheet in step S3 together

[0042] A composite sheet is prepared, wherein the composite sheet is composed of a PMMA sheet, a UV adhesive, a metal mesh, a UV adhesive and a PMMA sheet from bottom to top;

[0043] S5, pre-pressing the combined sheet obtained in step S4 under vacuum to remove bubbles;

[0044] S6, curing the combined sheets after degassing in step S5 under UV light to obtain shielding glass.

[0045] The PMMA sheet is a composite sheet of PMMA and modified PMMA, and the PMMA sheet includes 0-7.5wt% of modified PMMA. The preparation method of the modified PMMA includes:

[0046] (1) Add nano calcium carbonate to a 30 wt% sodium phosphate solution, let stand for 20-40 min, take out, and dry; immerse in octadecyltrichlorosilane liquid for 15-30 min, dry, and obtain modified nano calcium carbonate for later use;

[0047] (2) Add methyl methacrylate, polyvinyl pyrrolidone and initiator to the solvent, stir at 60-90°C for 1.5-3h, add zinc stearate and modified nano calcium carbonate prepared in step (1), continue stirring at 60-90°C for 3-4h, filter, take the filter residue, dry at 60-80°C for 12-24h, and granulate to obtain modified PMMA.

[0048] The present application provides a shielding glass prepared by a method for preparing shielding glass.

[0049] The technical problem solved by the present application is that the shielding window with acrylic as the substrate is not resistant to high temperature. Acrylic expands and absorbs water, and warps and deforms at the four corners in a high temperature and high humidity environment; and the bonding strength of the adhesive becomes lower in a high temperature and high humidity environment. As the thermal expansion and warping of the board produce internal stress, the bonding strength of the adhesive layer cannot offset the internal stress of the acrylic deformation, causing cracking. The adhesive is not resistant to high temperatures of 85°C, causing blistering and edge cracking. The present application selects PMMA board as the transparent substrate and UV glue as the adhesive material to improve the adhesion and light transmittance between the transparent substrate and the adhesive material. The high temperature resistance of the shielding glass is improved by modifying the PMMA board, selecting a suitable UV glue and UV curing process.

[0050] The raw materials used in the examples of this application are all commercially available, and their specific sources are as follows:

[0051] PMMA sheet, Sumitomo Chemical Industries, Ltd., Japan;

[0052] UV glue, Yantai Debang Technology Co., Ltd.;

[0053] Octadecyltrichlorosilane, Beijing Bailingwei Technology Co., Ltd.;

[0054] Zinc stearate, Shandong Yukang Chemical Co., Ltd.;

[0055] Polyvinylpyrrolidone, polyvinylpyrrolidone;

[0056] Methyl methacrylate, Sigma-Aldrich (Shanghai) Trading Co., Ltd.

[0057] In this application, the applicant compared the PMMA sheet produced by Evonik Degussa of Germany and the PMMA sheet produced by Sumitomo Chemical Industries, Ltd. of Japan through tests. After the high temperature test at 85°C for 48 hours, the PMMA of Sumitomo Chemical Industries, Ltd. of Japan did not deform, so the 1mm PMMA sheet of Sumitomo Chemical Industries, Ltd. of Japan was selected as the substrate. The UV glue used was the UV glue produced by Debon Company, with a viscosity of about 1200 mps. The transmittance of the UV glue used in this application under visible light with a wavelength of 550nm is above 99%, the curing shrinkage of the UV glue used in this application is about 2%, and the refractive index of the UV glue used in this application is about 1.48.

[0058] The method for preparing the shielding glass in Example 1 comprises the following steps:

[0059] S1. Take a metal mesh with an aperture of 80 mesh and a wire diameter of 0.05mm and two PMMA sheets with a thickness of 1mm. Cut the metal mesh and PMMA sheets into a size of 179mm*139mm in length and width, and clean them. Place the PMMA sheets on the operating table, use a glue dispenser to apply UV glue on the PMMA sheets, and let them stand for self-leveling for 10 minutes.

[0060] S2, covering the PMMA plate after the glue is dispensed in step S1 with a metal mesh for later use;

[0061] S3, repeat the operation of step S1 to obtain another PMMA sheet with glue applied, for later use;

[0062] S4, laminating the PMMA sheet in step S2 and the PMMA sheet in step S3 to obtain a composite sheet, so that the composite sheet is composed of PMMA sheet, UV glue, metal mesh, UV glue and PMMA sheet from bottom to top;

[0063] S5, pre-pressing the combined sheet obtained in step S4 to remove bubbles under vacuum; the vacuum degree is 0.08Mpa;

[0064] S6, curing the combined sheets after degassing in step S5 under UV light to obtain shielding glass, wherein the thickness of the two layers of UV glue is controlled to be 0.15 mm; the curing is divided into pre-curing and main curing, the pre-curing time is 30 seconds, and the main curing time is 2 hours; the UV light source is a xenon lamp light source, and the curing energy of the UV light source is 8000 mJ / cm 2 .

[0065] The method for preparing the shielding glass in Example 2 comprises the following steps:

[0066] S1. Take a metal mesh with an aperture of 80 mesh and a wire diameter of 0.05mm and two PMMA sheets with a thickness of 0.9mm. Cut the metal mesh and PMMA sheets into a size of 179mm*139mm in length and width, and clean them. Place the PMMA sheets on the operating table, use a glue dispenser to apply UV glue on the PMMA sheets, and let them stand for self-leveling for 10 minutes.

[0067] S2, covering the PMMA plate after the glue is dispensed in step S1 with a metal mesh for later use;

[0068] S3, repeat the operation of step S1 to obtain another PMMA sheet with glue applied, for later use;

[0069] S4, laminating the PMMA sheet in step S2 and the PMMA sheet in step S3 to obtain a composite sheet, so that the composite sheet is composed of PMMA sheet, UV glue, metal mesh, UV glue and PMMA sheet from bottom to top;

[0070] S5, pre-pressing the combined sheet obtained in step S4 to remove bubbles under vacuum; the vacuum degree is 0.08Mpa;

[0071] S6, curing the combined sheets after degassing in step S5 under UV light to obtain shielding glass, wherein the thickness of the two layers of UV glue is controlled to be 0.2 mm; the curing is divided into pre-curing and main curing, the pre-curing time is 60 seconds, and the main curing time is 3 hours; the UV light source adopts a xenon lamp light source, and the curing energy of the UV light source is 5000 mJ / cm 2 .

[0072] The method for preparing the shielding glass in Example 3 comprises the following steps:

[0073] S1. Take a metal mesh with an aperture of 80 mesh and a wire diameter of 0.05mm and two PMMA sheets with a thickness of 1.2mm. Cut the metal mesh and PMMA sheets into a size of 179mm*139mm in length and width, and clean them. Place the PMMA sheets on the operating table, use a glue dispenser to apply UV glue on the PMMA sheets, and let them stand for self-leveling for 10 minutes.

[0074] S2, covering the PMMA plate after the glue is dispensed in step S1 with a metal mesh for later use;

[0075] S3, repeat the operation of step S1 to obtain another PMMA sheet with glue applied, for later use;

[0076] S4, laminating the PMMA sheet in step S2 and the PMMA sheet in step S3 to obtain a composite sheet, so that the composite sheet is composed of PMMA sheet, UV glue, metal mesh, UV glue and PMMA sheet from bottom to top;

[0077] S5, pre-pressing the combined sheet obtained in step S4 to remove bubbles under vacuum; the vacuum degree is 0.08Mpa;

[0078] S6. The debubbled sheets in step S5 are cured under UV light to obtain shielding glass, wherein the thickness of the two layers of UV glue is controlled to be 0.1 mm; the curing is divided into pre-curing and main curing, the pre-curing time is 15 s, and the main curing time is 0.5 h; the UV light source is a xenon lamp light source, and the curing energy of the UV light source is 12000 mJ / cm 2 .

[0079] The method for preparing the shielding glass in Example 4 comprises the following steps:

[0080] S1. Take a metal wire mesh with an aperture of 80 mesh and a wire diameter of 0.05mm and two modified PMMA sheets with a thickness of 1mm. Cut the metal wire mesh and the modified PMMA sheets into a size of 179mm*139mm in length and width, and clean them. Place the modified PMMA sheets on the operating table, use a glue dispenser to apply UV glue on the modified PMMA sheets, and let them stand for self-leveling for 10 minutes.

[0081] S2, covering the modified PMMA sheet after the glue is dispensed in step S1 with a metal mesh for later use;

[0082] S3, repeat the operation of step S1 to obtain another modified PMMA sheet with glue applied, for standby use;

[0083] S4, laminating the modified PMMA sheet in step S2 and the modified PMMA sheet in step S3 to obtain a composite sheet, so that the composite sheet is, from bottom to top, the modified PMMA sheet, UV glue, metal mesh, UV glue and the modified PMMA sheet;

[0084] S5, pre-pressing the combined sheet obtained in step S4 to remove bubbles under vacuum; the vacuum degree is 0.08Mpa;

[0085] S6, curing the combined sheets after degassing in step S5 under UV light to obtain shielding glass, wherein the thickness of the two layers of UV glue is controlled to be 0.15 mm; the curing is divided into pre-curing and main curing, the pre-curing time is 30 seconds, and the main curing time is 2 hours; the UV light source is a xenon lamp light source, and the curing energy of the UV light source is 8000 mJ / cm 2 .

[0086] The modified PMMA plate in this embodiment is a composite plate obtained by melt-extruding modified PMMA and PMMA. The modified PMMA plate in this embodiment includes 6 wt % of modified PMMA.

[0087] The preparation method of modified PMMA comprises the following steps:

[0088] (1) Add nano calcium carbonate to a 30 wt% sodium phosphate solution, let stand for 30 min, take out, and dry; immerse in octadecyltrichlorosilane liquid for 25 min, dry, and obtain modified nano calcium carbonate for later use;

[0089] (2) Methyl methacrylate, polyvinyl pyrrolidone and initiator are added to the solvent, stirred at 80°C for 2 h, zinc stearate and the modified nano-calcium carbonate prepared in step (1) are added, and stirring is continued at 80°C for 3.5 h. The mixture is filtered, the filter residue is taken, and dried at 65°C for 24 h. The mixture is granulated to obtain modified PMMA.

[0090] The raw materials of modified PMMA include: 80 parts by weight of methyl methacrylate, 10 parts by weight of modified nano calcium carbonate, 3.5 parts by weight of zinc stearate, 3 parts by weight of polyvinyl pyrrolidone and 0.6 parts by weight of azobisisobutyronitrile (initiator); wherein, in the preparation process of modified nano calcium carbonate, the weight ratio of nano calcium carbonate, sodium phosphate solution and octadecyltrichlorosilane is 10:45:20.

[0091] Embodiment 5 is based on Embodiment 4, except that: the preparation method of the shielding glass in Embodiment 5 comprises the following steps:

[0092] S1. Take a metal wire mesh with an aperture of 80 mesh and a wire diameter of 0.05mm and two modified PMMA sheets with a thickness of 0.9mm. Cut the metal wire mesh and the modified PMMA sheets into a size of 179mm*139mm in length and width, and clean them. Place the modified PMMA sheets on the operating table, use a glue dispenser to apply UV glue on the modified PMMA sheets, and let them stand for self-leveling for 10 minutes.

[0093] S2, covering the modified PMMA sheet after the glue is dispensed in step S1 with a metal mesh for later use;

[0094] S3, repeat the operation of step S1 to obtain another modified PMMA sheet with glue applied, for standby use;

[0095] S4, laminating the modified PMMA sheet in step S2 and the modified PMMA sheet in step S3 to obtain a composite sheet, so that the composite sheet is, from bottom to top, the modified PMMA sheet, UV glue, metal mesh, UV glue and the modified PMMA sheet;

[0096] S5, pre-pressing the combined sheet obtained in step S4 to remove bubbles under vacuum; the vacuum degree is 0.08Mpa;

[0097] S6, curing the combined sheets after degassing in step S5 under UV light to obtain shielding glass, wherein the thickness of the two layers of UV glue is controlled to be 0.2 mm; the curing is divided into pre-curing and main curing, the pre-curing time is 60 seconds, and the main curing time is 3 hours; the UV light source adopts a xenon lamp light source, and the curing energy of the UV light source is 5000 mJ / cm 2 .

[0098] Embodiment 6 is based on Embodiment 4, except that: the method for preparing the shielding glass in Embodiment 6 comprises the following steps:

[0099] S1. Take a metal wire mesh with an aperture of 80 mesh and a wire diameter of 0.05mm and two modified PMMA sheets with a thickness of 1.2mm. Cut the metal wire mesh and the modified PMMA sheets into a size of 179mm*139mm in length and width, and clean them. Place the modified PMMA sheets on the operating table, use a glue dispenser to apply UV glue on the modified PMMA sheets, and let them stand for self-leveling for 10 minutes.

[0100] S2, covering the modified PMMA sheet after the glue is dispensed in step S1 with a metal mesh for later use;

[0101] S3, repeat the operation of step S1 to obtain another modified PMMA sheet with glue applied, for standby use;

[0102] S4, laminating the modified PMMA sheet in step S2 and the modified PMMA sheet in step S3 to obtain a composite sheet, so that the composite sheet is, from bottom to top, the modified PMMA sheet, UV glue, metal mesh, UV glue and the modified PMMA sheet;

[0103] S5, pre-pressing the combined sheet obtained in step S4 to remove bubbles under vacuum; the vacuum degree is 0.08Mpa;

[0104] S6. The debubbled sheets in step S5 are cured under UV light to obtain shielding glass, wherein the thickness of the two layers of UV glue is controlled to be 0.1 mm; the curing is divided into pre-curing and main curing, the pre-curing time is 15 s, and the main curing time is 0.5 h; the UV light source is a xenon lamp light source, and the curing energy of the UV light source is 12000 mJ / cm 2 .

[0105] Example 7 is based on Example 4, except that: in Example 7, modified nano-calcium carbonate is not used in the modified PMMA raw material, and nano-calcium carbonate and methyl methacrylate are directly used for in-situ compounding, that is, the preparation method of modified PMMA in Example 7 includes the following steps:

[0106] Methyl methacrylate, polyvinyl pyrrolidone and initiator are added to the solvent, stirred at 80°C for 2 hours, zinc stearate and nano calcium carbonate are added, and stirring is continued at 80°C for 3.5 hours. The mixture is filtered, the filter residue is taken, and dried at 65°C for 24 hours. The mixture is granulated to obtain modified PMMA.

[0107] The raw materials for modifying PMMA in Example 7 include: 80 parts by weight of methyl methacrylate, 10 parts by weight of nano-calcium carbonate, 3.5 parts by weight of zinc stearate, 3 parts by weight of polyvinyl pyrrolidone and 0.6 parts by weight of azobisisobutyronitrile (initiator).

[0108] Performance testing:

[0109] The performance of the shielding glasses prepared in Examples 1-7 was tested under high temperature, low temperature, temperature shock, damp heat and salt spray conditions.

[0110] 1. According to the requirements of the reference standard GJB150.3A-2009, the shielding glasses prepared in Examples 1-7 were observed to have bubbles and debonding at a constant temperature of 85°C for 48 hours.

[0111] 2. According to the requirements of the reference standard GJB150.4A-2009, the shielding glasses prepared in Examples 1-7 were kept at a constant temperature of -55°C for 24 hours to observe whether there were bubbles and debonding.

[0112] 3. According to the requirements of the reference standard GJB150.5A-2009, ten cycles were carried out at a temperature of -45-70°C to observe whether the shielding glasses prepared in Examples 1-7 had bubbles and debonding.

[0113] 4. According to the requirements of the reference standard GJB150.9A-2009, ten cycles were performed under a temperature shock of 30°C-60°C at 95% humidity to observe whether the shielding glasses prepared in Examples 1-7 had bubbles and debonding.

[0114] 5. According to the requirements of the reference standard GJB150.11A-2009, the shielding glasses prepared in Examples 1-7 were observed for bubbles and debonding under 5% NaCl salt spray for 96 hours.

[0115] The test results are shown in Table 1.

[0116] Table 1

[0117] High temperature experiment Low temperature experiment Temperature shock test Wet heat test Salt spray test GJB150.3A GJB150.4A GJB150.5A GJB150.9A GJB150.11A Example 1 90℃, 48h without bubbles or debonding -55℃, no bubbles or debonding for 24h No bubbles, no debonding 95% humidity, 30-70℃ cycle, no bubbles or debonding No bubbles, no debonding Example 2 85℃, no bubbles or debonding for 48h -55℃, a small amount of bubbles appear in 24 hours No bubbles, no debonding 95% humidity, 30-60℃ cycle, no bubbles or debonding No bubbles, no debonding Example 3 85℃, no bubbles or debonding for 48h -55℃, no bubbles or debonding for 24h No bubbles, no debonding 95% humidity, 30-60℃ cycle, no bubbles or debonding No bubbles, no debonding Example 4 100℃, 48h without bubbles or debonding -55℃, no bubbles or debonding for 24h No bubbles, no debonding 95% humidity, 30-75℃ cycle, no bubbles or debonding No bubbles, no debonding Example 5 115℃, 48h without bubbles or debonding No bubbles, no debonding No bubbles, no debonding 95% humidity, 30-85℃ cycle, no bubbles or debonding No bubbles, no debonding Example 6 100℃, 48h without bubbles or debonding -55℃, no bubbles or debonding for 24h A small amount of bubbles appear 95% humidity, 30-60℃ cycle, no bubbles or debonding No bubbles, no debonding Example 7 85℃, more bubbles appear after 48h -55℃, glue peeling occurs after 24h Bubbles and debonding 95% humidity, 30-60℃ cycle, glue peeling occurs No bubbles, no debonding

[0118] By analyzing the data in Table 1, the shielding glass made of PMMA sheets in Examples 1-3 has good high temperature resistance, and no bubbles or debonding will occur at 85°C for 48 hours; by comparing Examples 1-3 with Examples 4-6, it can be obtained that after replacing the PMMA sheets with modified PMMA sheets, the high temperature resistance of the shielding glass is further improved, and no bubbles or debonding will occur at 115°C for 48 hours. At the same time, in Examples 1-3, the shielding glass prepared in Example 1 performs better in high temperature experiments and wet heat experiments, and in Examples 4-6, the performance of Example 5 is better. Therefore, after replacing the PMMA sheets with modified PMMA sheets, the corresponding preparation process should also be adjusted accordingly to further improve the high temperature resistance and other weather resistance of the shielding glass. In summary, the shielding glass prepared by the preparation process in the present application selects PMMA sheet as the transparent substrate and selects UV glue as the adhesive material, which improves the adhesion and light transmittance between the transparent substrate and the adhesive material. The high temperature resistance and weather resistance of the shielding glass are improved by modifying the PMMA sheet, selecting suitable UV glue and UV curing process.

[0119] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing shielding glass, characterized in that: The following steps are involved: S1. Place a PMMA sheet on the operating table, apply UV glue on the PMMA sheet, and let it stand for self-leveling; S2. Cover the cut metal mesh on the PMMA sheet after the glue application in step S1, and set it aside; S3. Repeat the operation of step S1 to obtain another PMMA sheet after the glue application, and set it aside; S4. Bond the PMMA sheet in step S2 and the PMMA sheet in step S3 to obtain a composite sheet, so that the composite sheet is PMMA sheet, UV glue, metal mesh, UV glue and PMMA sheet from bottom to top; S5. Pre-press the composite sheet obtained in step S4 under vacuum to remove bubbles; S6. Cure the composite sheet after the bubbles are removed in step S5 under UV light to obtain shielding glass; The raw material of the PMMA sheet includes 0-7.5wt% of modified PMMA; The preparation method of the modified PMMA comprises: (1) adding nano calcium carbonate into a 30wt% sodium phosphate solution, standing for 20-40min, taking out, and drying; Immerse in octadecyltrichlorosilane liquid for 15-30 minutes, dry to obtain modified nano calcium carbonate, and set aside; (2) add methyl methacrylate, polyvinyl pyrrolidone and initiator to the solvent, stir at 60-90°C for 1.5-3h, add zinc stearate and the modified nano calcium carbonate obtained in step (1), continue to stir at 60-90°C for 3-4h, filter, take the filter residue, dry at 60-80°C for 12-24h, granulate to obtain modified PMMA.

2. The method for preparing shielding glass according to claim 1, characterized in that: In step S6, curing is divided into pre-curing and main curing, the pre-curing time is 15-60 seconds, and the main curing time is 0.5-3 hours.

3. The method for preparing shielding glass according to claim 2, characterized in that: In step S6, the pre-curing time is 30 seconds and the main curing time is 2 hours.

4. The method for preparing shielding glass according to claim 1, characterized in that: In step S6, the UV light source is selected from at least one of a mercury lamp light source, an LED light source, and a xenon lamp light source, and the curing energy is 5000-12000 mJ / cm 2 .

5. The method for preparing shielding glass according to claim 1, characterized in that: The viscosity of the UV glue is 800 mps-1500 mps.

6. The method for preparing shielding glass according to claim 1, characterized in that: The thickness of a single layer of PMMA sheet in the composite sheet is 0.9-1.2 mm, and the thickness of a single layer of UV glue in the composite sheet is 0.1-0.2 mm.

7. The method for preparing shielding glass according to claim 1, characterized in that: The modified PMMA comprises the following raw materials by weight: 60-90 parts of methyl methacrylate, 6-13 parts of modified nano-calcium carbonate, 3-5 parts of zinc stearate, 1.5-3.5 parts of polyvinyl pyrrolidone and 0.5-0.9 parts of initiator; in the preparation process of the modified nano-calcium carbonate, the weight ratio of the nano-calcium carbonate, the sodium phosphate solution and the octadecyltrichlorosilane is: 8-12:40-60:15-25.

8. Shielding glass made according to the method for making shielding glass according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method for TiO2-g-PMMA

    CN109485807A

  • Production technology of electromagnetic shielding glass used for military window

    CN109849456A

  • Acrylic pouring silk screen shielding glass and preparation method thereof

    CN113150481A